Pembuatan Model DCS pada Tangan Robot Pemisah Benda Menggunakan PLC Berbasis HMI - Syufrijal, Syufrijal (LPPM Universitas Negeri Jakarta, 2018)
In this research will be made a model of DCS (Distributed Control System) by using a PLC interface integrated with HMI (human machine interface) for controlling a plant in the form of a robot hand and object separator monitoring. Control tool is using 2 pieces of OMRON PLC. CJ1M used to control a robot hand moves to the right/left, clamping/releasing objects, up/down so the metal/non-metals can be separated from the zone to the stock of goods in conveyor1/conveyor2. Movements up/down robotic hand using a pneumatic system. CSG1H conveyor1/conveyor2 used to control motors, driving things forward/backward in conveyor1/conveyor2. Metal object/non-metal will be separated again by height (low, medium and high). Metal object/non-metal with low and high altitude will be moved to the zone while the stock of goods reject metal/non-metal with a height being will continue to run on top of the zone towards the stock of goods conveyor1/conveyor2 metal/non-metals. The use of HMI aims to facilitate the user in the process of monitoring and control via the touch screen. From the results of tests performed, the PLC can control the robot hand separator objects automatically according to the desired job description and work processes in the system can be controlled and monitored via touch screen HMI program. Dalam penelitian ini dibuat suatu model DCS (Distributed Control System) dengan menggunakan PLC yang terintegrasi dengan antar muka HMI (human machine interface) untuk mengontrol suatu plant berupa tangan robot pemisah benda. Pengendalian alat ini menggunakan 2 buah PLC omron. CJ1M digunakan untuk mengendalikan tangan robot agar benda logam/non-logam dapat dipisahkan dari zona stock barang menuju konveyor1 atau konveyor2. Pergerakan naik/turunnya tangan robot menggunakan sistem pneumatik sedangkan CSG1H digunakan untuk mengendalikan motor konveyor1/konveyor2, pendorong benda maju/mundur di konveyor1/konveyor2. Benda logam/non-logam akan dipisahkan kembali berdasarkan ketinggian (rendah, sedang dan tinggi). Benda logam/non-logam dengan ketinggian rendah dan tinggi akan dipindahkan menuju zona stock barang reject sedangkan benda logam/non-logam dengan ketinggian sedang akan terus berjalan di atas konveyor1/konveyor2 menuju zona stock barang logam/non-logam. Dari hasil pengujian yang dilakukan, kedua PLC dapat mengendalikan tangan robot pemisah benda secara otomatis sesuai dengan deskripsi kerja yang diinginkan dan proses kerja sistem dapat termonitor di layar touch screen melalui program HMI.